Composite, catalyst ink, and method for producing composite

By preparing a complex with a mesecopide and tannel of molybdenum and ban dioxide, the problem of insufficient catalyst materials in existing technologies has been solved, and the performance of hydrogen analyzes is achieved.

CN119384315APending Publication Date: 2025-01-28DIC CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380050399.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-15
Filing Date
2023-09-15
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

There is still room for research in the prior art on providing novel catalyst materials containing molybdenum disulfide, especially in the performance of hydrogen evolution catalysts, which have not fully met expectations.

Method used

By preparing complexes containing 3R crystal structures and molybdenum dioxide, combined with specific microcrystalline sizes and surface area range to form a complex with excellent catalyst performance.

Benefits of technology

The high performance of the hydrogen analysis catalyst is achieved, which improves the activity and efficiency of the catalyst, and is suitable for hydrogen analysis such as hydrolysis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119384315A_ABST
    Figure CN119384315A_ABST
Patent Text Reader

Abstract

The present invention provides a composite containing molybdenum disulfide and molybdenum trioxide, the molybdenum disulfide containing a 3R crystal structure, and the content ratio of a molybdenum trioxide equivalent value (B) calculated from the molybdenum content determined by XRF analysis of the composite with respect to the total mass of the composite being 5-90 mass%. The invention provides a catalyst ink which comprises the composite and a solvent. Also provided is a method for producing the composite, which comprises a firing step in which molybdenum trioxide is heated at a temperature of 400 DEG C or less in the presence of a sulfur source.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a composite material, a catalyst ink, and a method for manufacturing the composite material.

[0002] This application claims priority based on Japanese Patent Application No. 2022-146943 filed in Japan on September 15, 2022, the contents of which are incorporated herein by reference. Background Art

[0003] In the process of working to solve environmental and energy resource problems, water electrolysis technology has attracted much attention as a technology that can use electricity from renewable energy and produce hydrogen from water.

[0004] Layered transition metal chalcogenides, represented by molybdenum disulfide (MoS2), are highly anticipated as a material that is inexpensive, abundant in resources, and has high catalytic activity.

[0005] Although such catalytic activity can be improved to a certain extent by refining or depolymerizing molybdenum sulfide, which is obtained by any production method such as sulfiding molybdenum oxide, the expected performance may not be obtained by this alone. Therefore, in order to exert more excellent performance in accordance with various purposes of use, the production method of molybdenum sulfide in a specific shape such as a single layer, a nanoflower, and a fullerene-like shape has been studied (see Patent Documents 1-2).

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2004-277199

[0009] Patent Document 2: Japanese Patent Application No. 2004-512250 Summary of the invention

[0010] Problems to be solved by the invention

[0011] However, there is still room for research on providing novel catalyst materials comprising molybdenum disulfide.

[0012] The object of the present invention is to provide a composite material that can be used as a catalyst, especially as a hydrogen evolution catalyst, a catalyst ink, and a method for producing the composite material.

[0013] Methods for solving problems

[0014] The present invention has the following aspects.

[0015] <1> A composite comprising molybdenum disulfide and molybdenum trioxide,

[0016] The above molybdenum disulfide comprises a 3R crystal structure,

[0017] The content of the molybdenum trioxide equivalent value (B) calculated from the molybdenum content determined by XRF analysis of the composite is 5 to 90% by mass relative to the total mass of the composite.

[0018] <2> The composite material according to <1> above, wherein the average crystallite size of the molybdenum disulfide determined from a peak at 2θ=14.4°±0.5° obtained by X-ray diffraction measurement is 50 nm or less.

[0019] <3> The composite according to <1> or <2>, wherein the average crystallite size of the molybdenum trioxide determined from a peak at 2θ=12.7°±0.5° obtained by X-ray diffraction measurement is 50 nm or less.

[0020] <4> The composite according to any one of <1> to <3>, wherein the median particle size D of the composite determined by a dynamic light scattering method is 50 Below 1000 nm.

[0021] <5> The composite according to any one of <1> to <4>, wherein the composite has a specific surface area of ​​5 m 2 / g and above 200 m 2 / g or less.

[0022] <6> The composite material according to any one of <1> to <5>, wherein the ratio (A / B) of the molybdenum disulfide conversion value (A) calculated based on the sulfur content determined by XRF analysis of the composite material to the molybdenum trioxide conversion value (B) calculated based on the molybdenum content determined by XRF analysis of the composite material is 0.1 to 50 on a mass basis.

[0023] <7> The composite material according to any one of <1> to <6>, wherein the content of molybdenum disulfide conversion value (A) calculated from the sulfur content determined by XRF analysis of the composite material is 10 to 95% by mass relative to the total mass of the composite material.

[0024] <8> The composite according to any one of <1> to <7>, wherein the ratio of the content of elemental sulfur to the total content of sulfur elements in the composite is 10% or less on a molar basis.

[0025] <9> The composite according to any one of <1> to <8>, which is used as a hydrogen generating catalyst.

[0026] <10> A catalyst ink comprising the composite according to any one of <1> to <9> and a solvent.

[0027] <11> A method for producing the composite material according to any one of <1> to <9>, comprising a calcining step of heating molybdenum trioxide at a temperature of 400° C. or less in the presence of a sulfur source.

[0028] <12> The method for producing a composite material according to <11>, further comprising a washing step of removing the sulfur source after the calcining step.

[0029] <13> The method for producing a composite material according to <11> or <12>, wherein the molybdenum trioxide has a specific surface area of ​​10 m 2 / g and above 100 m 2 / g or less.

[0030] Effects of the Invention

[0031] According to the present invention, a composite material that can be used as a catalyst, particularly a hydrogen evolution catalyst, a catalyst ink, and a method for producing the composite material can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] FIG. 1 is a schematic diagram showing an example of an apparatus for producing molybdenum trioxide particles that can be used as a raw material for the composite of the embodiment.

[0033] 2 ] is a diagram showing the X-ray diffraction (XRD) patterns of the particles obtained in Examples 1 to 5 and Reference Example 1 superimposed on each other.

[0034] [ FIG. 3 ] is a transmission electron microscope (TEM) image of the composite particles obtained in Example 1.

[0035] FIG. 4 is an image showing a high-angle annular dark field scanning transmission electron microscope (HAADF-STEM) image of the composite particles obtained in Example 1 and the results of elemental mapping using energy dispersive X-ray spectroscopy (EDS). DETAILED DESCRIPTION

[0036] Hereinafter, embodiments of the composite, catalyst ink, and method for producing the composite according to the present invention will be described.

[0037] <<Compound>>

[0038] The composite of the embodiment includes molybdenum disulfide and molybdenum trioxide, the molybdenum disulfide includes a 3R crystal structure, and the content of the molybdenum trioxide conversion value (B) calculated from the molybdenum content determined by XRF analysis of the composite is 5 to 90 mass % relative to the total mass of the composite.

[0039] The composite of the embodiment includes both molybdenum disulfide (MoS 2 ) and molybdenum trioxide (MoO 3 ).

[0040] By including MoS2 and MoO3 in the composite, the catalyst performance is improved due to the electron exchange at the interface of MoS2 and MoO3.

[0041] In addition, the molybdenum disulfide of the composite of the embodiment includes a 3R crystal structure, which contributes to improving the catalyst performance. The crystal structure of molybdenum disulfide is described in detail below.

[0042] As shown in the examples described below, the composite particles containing molybdenum disulfide and molybdenum trioxide have improved catalytic performance as a hydrogen evolution catalyst compared to particles containing only molybdenum disulfide, particles containing only molybdenum trioxide, or particles containing both molybdenum disulfide and molybdenum trioxide but not satisfying the above-mentioned molybdenum trioxide conversion value (B).

[0043] The existence form of MoS2 and MoO3 in the composite of the embodiment is not particularly limited, but according to the analysis results of energy dispersive X-ray spectroscopy (EDS) shown in the examples described later, it can be confirmed that the closer the area is to the surface of the composite particle, the higher the S element content is.

[0044] Therefore, in the composite of the embodiment, MoS2 segregation may also exist on the surface of the composite. The so-called MoS2 segregation exists on the surface of the composite, which means that the surface of the composite has more MoS2 than the internal distribution of the composite. In addition, the surface of the composite may have less MoO3 than the internal distribution of the composite.

[0045] The composite of the embodiment contains molybdenum disulfide (MoS2). The composite of the embodiment preferably contains 10 to 95 mass % of molybdenum disulfide (MoS2) relative to the total mass (100 mass %) of the composite, more preferably 15 to 50 mass %, and even more preferably 20 to 45 mass %.

[0046] The content of molybdenum disulfide (MoS 2 ) in the composite material of the embodiment may be a value calculated by XRF analysis as described below.

[0047] In the composite of the embodiment, the content of molybdenum disulfide conversion value (A) calculated from the sulfur content determined by XRF analysis of the composite is preferably 10 to 95 mass %, more preferably 15 to 50 mass %, and even more preferably 20 to 45 mass % relative to the total mass of the composite.

[0048] In a composite material having a content ratio of molybdenum disulfide conversion value (A) within the above numerical range, the content ratio of molybdenum sulfide is good, and the catalytic activity derived from molybdenum sulfide is further effectively exerted.

[0049] The molybdenum disulfide conversion value (A) refers to a value obtained by performing XRF analysis on the composite and converting the sulfur content into MoS2 amount using a MoS2 conversion calibration curve, and the value obtained from the MoS2 amount.

[0050] The composite of the embodiment contains molybdenum trioxide (MoO3). The composite of the embodiment may contain 5 to 90 mass % of molybdenum trioxide (MoO3) relative to the total mass (100 mass %) of the composite, more preferably 50 to 85 mass %, and even more preferably 55 to 80 mass %.

[0051] The content of molybdenum trioxide (MoO 3 ) in the composite material of the embodiment may be a value calculated by XRF analysis as described below.

[0052] In the composite of the embodiment, the content of molybdenum trioxide conversion value (B) calculated from the molybdenum content determined by XRF analysis of the composite is 5 to 90 mass %, preferably 50 to 85 mass %, more preferably 55 to 80 mass % relative to the total mass of the composite.

[0053] In the composite having the content of molybdenum trioxide equivalent (B) within the above numerical range, the content ratio of the molybdenum oxide is good, and the catalytic activity derived from the molybdenum oxide is more effectively exerted.

[0054] The molybdenum trioxide conversion value (B) refers to a value obtained by performing XRF analysis on the composite to determine the molybdenum content, converting the molybdenum content using a MoO3 conversion calibration curve to obtain the MoO3 amount.

[0055] It should be noted that the composite of the embodiment also contains molybdenum in the form of MoS2. Therefore, the MoS2 conversion value is first calculated as described above, and then the molybdenum corresponding to the MoS2 conversion value is subtracted, and the obtained molybdenum amount is used to calculate the molybdenum trioxide conversion value (B).

[0056] The composite of the embodiment may preferably have a content of 10 to 95% by mass of the molybdenum disulfide equivalent (A) relative to the total mass of the composite, and a content of 5 to 90% by mass of the molybdenum trioxide equivalent (B) relative to the total mass of the composite.

[0057] In the composite of the embodiment, the content of the molybdenum disulfide equivalent (A) relative to the total mass of the composite may more preferably be 15 to 50 mass %, and the content of the molybdenum trioxide equivalent (B) relative to the total mass of the composite may more preferably be 50 to 85 mass %.

[0058] The composite of the embodiment may further preferably have a content of 20 to 45% by mass of the molybdenum disulfide equivalent (A) relative to the total mass of the composite, and a content of 55 to 80% by mass of the molybdenum trioxide equivalent (B) relative to the total mass of the composite.

[0059] The ratio (A / B) of the molybdenum disulfide conversion value (A) calculated from the sulfur content determined by XRF analysis of the composite to the molybdenum trioxide conversion value (B) calculated from the molybdenum content determined by XRF analysis of the composite is preferably 0.1 or more, more preferably 0.2 or more, further preferably 0.25 or more, and particularly preferably 0.3 or more, on a mass basis. In addition, the ratio (A / B) is preferably 50 or less, more preferably 25 or less, further preferably 3 or less, and particularly preferably less than 1.

[0060] As an example of the numerical range of the numerical value of the above ratio (A / B), it may be 0.1 or more and 50 or less, 0.2 or more and 25 or less, 0.25 or more and 3 or less, or 0.3 or more and less than 1.

[0061] In a composite having the ratio (A / B) within the above numerical range, the content ratio of the molybdenum oxide and the molybdenum sulfide is well balanced, and the amount of the interface contributing to the catalytic activity is appropriate, so the catalytic activity can be more effectively exerted.

[0062] The average crystallite size of the molybdenum disulfide contained in the composite, determined from the peak at 2θ=14.4°±0.5° obtained by X-ray diffraction measurement, is preferably 50 nm or less, preferably 40 nm or less, more preferably 30 nm or less, further preferably 20 nm or less, particularly preferably 10 nm or less, and particularly preferably less than 6 nm.

[0063] The peak at 2θ=14.4°±0.5° is attributed to the (002) plane or (003) plane of molybdenum disulfide (MoS2). By including MoS2 with a smaller average crystallite size below the upper limit, the catalyst active sites such as interfaces and defects that contribute to the catalyst activity are increased, and the catalyst performance is improved.

[0064] The lower limit of the average crystallite size of molybdenum disulfide determined from the peak at 2θ=14.4°±0.5° obtained by X-ray diffraction measurement may be, for example, 1 nm or more, 2 nm or more, or 3 nm or more.

[0065] As an example of the numerical range of the above-mentioned numerical value of the average crystallite size calculated based on the peak of 2θ=14.4°±0.5° obtained by X-ray diffraction measurement of the above-mentioned molybdenum disulfide, it can be greater than 1 nm and less than 50 nm, greater than 2 nm and less than 40 nm, greater than 2 nm and less than 30 nm, greater than 3 nm and less than 20 nm, greater than 3 nm and less than 10 nm, or greater than 3 nm and less than 6 nm.

[0066] The average crystallite size of the molybdenum trioxide contained in the composite, determined from the peak at 2θ=12.7°±0.5° obtained by X-ray diffraction measurement, is preferably 50 nm or less, more preferably 40 nm or less, further preferably 30 nm or less, and particularly preferably 20 nm or less.

[0067] The peak at 2θ=12.7°±0.5° is attributed to the (020) plane of molybdenum trioxide (MoO3). By including MoO3 having a smaller average crystallite size than the upper limit, the number of catalyst active sites such as interfaces and defects that contribute to catalyst activity increases, and the catalyst performance is improved.

[0068] The lower limit of the average crystallite size of the molybdenum trioxide determined from the peak at 2θ=12.7°±0.5° obtained by X-ray diffraction measurement may be, for example, 1 nm or more, 2 nm or more, or 3 nm or more.

[0069] As an example of the numerical range of the above-mentioned numerical value of the average crystallite size calculated based on the peak of 2θ=12.7°±0.5° obtained by X-ray diffraction measurement of the above-mentioned molybdenum trioxide, it can be greater than 1 nm and less than 50 nm, greater than 2 nm and less than 40 nm, greater than 3 nm and less than 30 nm, or greater than 3 nm and less than 20 nm.

[0070] The above average crystallite size in the composite of the embodiment can be specified by the following measurement method.

[0071] [Determination of crystallite size]

[0072] The measurement is performed using an X-ray diffraction apparatus (e.g., SmartLab 9 kW manufactured by Rigaku Co., Ltd.), a scintillation counter as a detector, and analytical software (e.g., PDXL2). The measurement method is the 2θ / θ method, and the average crystallite size is calculated using the Scherrer equation based on the half-width of the peak that appears in the corresponding range of 2θ=14.4°±0.5° or 2θ=12.7°±0.5°. As measurement conditions, the scanning speed (2θ) is 2.0° / min, the scanning range (2θ) is 10-70°, the step (2θ) is 0.02°, and the device standard width is set to none.

[0073] The composite material of the embodiment may be a particulate structure (composite particles).

[0074] The median particle size D of the composite according to the embodiment obtained by dynamic light scattering method is 50 It is preferably 1000 nm or less, more preferably 800 nm or less, and further preferably 600 nm or less.

[0075] The median particle size D 50 A composite having an activity equal to or less than the above upper limit can more effectively exhibit catalytic efficiency.

[0076] The median particle size D of the composite according to the embodiment obtained by the dynamic light scattering method is 50 As an example, it may be greater than 20 nm, greater than 40 nm, greater than 100 nm, or greater than 300 nm.

[0077] The median particle size D of the composite of the embodiment obtained by dynamic light scattering method is 50 An example of the numerical range of the above numerical value may be greater than 20 nm and less than 1000 nm, greater than 40 nm and less than 800 nm, greater than 100 nm and less than 600 nm, or greater than 300 nm and less than 600 nm.

[0078] The median particle size D of the composite according to the embodiment calculated by the dynamic light scattering method is 50 The particle size distribution can be obtained as the particle size at which the volume cumulative % ratio is 50% by wet measurement using a dynamic light scattering particle size distribution analyzer (eg Nanotrac Wave II manufactured by MicrotracBEL) using acetone as a medium.

[0079] The specific surface area of ​​the composite of the embodiment measured by the BET method is preferably 5 m2 / g or more, more preferably 10 m 2 / g or more, more preferably 15 m 2 / g or more, particularly preferably 20 m 2 / g or above.

[0080] The composite having a specific surface area equal to or greater than the lower limit has a larger specific surface area, and thus has more catalyst active sites, and facilitates the movement of substances in the reaction system, thereby further effectively improving the catalyst efficiency.

[0081] The specific surface area of ​​the composite of the embodiment measured by the BET method may be, for example, 200 m 2 / g or less, and can also be 100 m 2 / g or less.

[0082] An example of the numerical range of the above-mentioned numerical value of the specific surface area of ​​the composite of the embodiment measured by the BET method is 5 m 2 / g and above 200 m 2 / g or less, can be 10 m 2 / g and above 200 m 2 / g or less, also 15 m 2 / g and above 100 m 2 / g or less, and can also be 20 m 2 / g and above 100 m 2 / g or less.

[0083] In this specification, the specific surface area is measured by a specific surface area meter (for example, BELSORP-mini manufactured by Microtrac BEL), and the surface area per 1 g of the sample measured by the BET method (Brunauer-Emmett-Teller method) is calculated as the specific surface area (m 2 / g).

[0084] The ratio of the content of elemental sulfur to the total content of sulfur in the composite (100%) is preferably 10% or less, more preferably 5% or less on a molar basis.

[0085] It should be noted that the composite of the embodiment can be provided in the form of an aggregate of composite particles (e.g., powder). As long as the aggregate contains molybdenum disulfide (MoS2), it can contain one or more MoS x (X = 1 to 3) represented by molybdenum sulfide. Similarly, as long as the aggregate contains molybdenum trioxide (MoO3), it may contain one or more molybdenum trioxides such as MoO2, Mo9O 25 Represents molybdenum oxide.

[0086] In addition, for example, the above average crystallite size, D 50 , specific surface area, XRF analysis, the following conversion rate R C The correlation value of can be a value measured using an aggregate (eg, powder) of composite particles as a sample.

[0087] Conversion rate R of the composite of the embodiment to MoS2 C It is preferably 90% or less, more preferably 60% or less, and further preferably 50% or less.

[0088] The conversion rate R to MoS2 C When the content is equal to or less than the above upper limit, the catalyst performance can be more effectively exhibited.

[0089] Conversion rate R of the composite of the embodiment to MoS2 C It is preferably 10% or more, more preferably 15% or more, and further preferably 20% or more.

[0090] The conversion rate R to MoS2 C When the content is not less than the above lower limit, the catalyst performance can be more effectively exhibited.

[0091] The conversion rate R of the composite as an embodiment C As an example of the above numerical range, the conversion rate R C It may be 10% or more and 90% or less, 15% or more and 60% or less, or 20% or more and 50% or less.

[0092] Conversion rate R of the composite of the embodiment to MoS2 C It can be obtained by the RIR (reference intensity) method based on the spectrum data obtained by measuring the composite of the embodiment by X-ray diffraction (XRD). The RIR value K of molybdenum disulfide (MoS2) can be used. A , and the integrated intensity I of the peak near 2θ=14.4°±0.5° attributable to the (002) plane or (003) plane of molybdenum disulfide (MoS2) A , and each molybdenum oxide (MoO3 as a raw material and Mo9O as a reaction intermediate) 25 、Mo4O 11 , MoO2, etc.) B and each molybdenum oxide (MoO3 as raw material and Mo9O as reaction intermediate) 25 、Mo4O 11 , MoO2, etc.) is the integrated intensity I B The conversion rate R to MoS2 is calculated by the following formula (1): C .

[0093] R C (%) = (I A / K A ) / ((I A / K A )+Σ(I B / K B ))×100(1)

[0094] Here, the RIR values ​​may be values ​​listed in the Inorganic Crystal Structure Database (ICSD) (created by the Japan Association for International Chemical Information), and the analysis may be performed using comprehensive powder X-ray analysis software (eg, PDXL2, manufactured by Rigaku Corporation).

[0095] The crystal structure of molybdenum trioxide contained in the composite of the embodiment may include α crystals, or may include α crystals and β crystals.

[0096] In the composite of the embodiment, the α crystal structure of molybdenum trioxide can be confirmed by the presence of a peak of the (021) plane of the α crystal of MoO3 (2θ: around 27.32°, No. 166363 (Inorganic Crystal Structure Database, ICSD)). In addition, the β crystal structure can be confirmed by the presence of a peak of the (011) plane of the β crystal of MoO3 (2θ: around 23.01°, No. 86426 (Inorganic Crystal Structure Database, ICSD)) in the following spectrum obtained by powder X-ray diffraction (XRD) using Cu-Kα rays as an X-ray source.

[0097] In the spectrum obtained by powder X-ray diffraction (XRD) using Cu-Kα rays as an X-ray source of the composite of the embodiment, the ratio of the peak intensity attributable to the (011) plane of the β crystal of MoO3 to the peak intensity attributable to the (021) plane of the α crystal of MoO3 (β(011) / α(021)) is preferably 0.1 or more.

[0098] The peak intensity attributable to the (011) plane of the β crystal of MoO 3 and the peak intensity attributable to the (021) plane of the α crystal of MoO 3 were read at their respective maximum intensities, and the above ratio (β(011) / α(021)) was determined.

[0099] In the MoO 3 of the composite of the embodiment, the ratio (β(011) / α(021)) is preferably 0.1 to 10.0, more preferably 0.2 to 10.0, and particularly preferably 0.4 to 10.0.

[0100] The content of α crystals of MoO 3 in the composite of the embodiment is not particularly limited, and may be 20% or more, 50% or more, 70% or more, 80% or more, or 100%.

[0101] The content of MoO3 α crystals in a mixture of MoO3 α crystals and β crystals can be calculated by the RIR (reference intensity) method based on the obtained spectrum data. The RIR value K of MoO3 α crystals can be used. A and the integrated intensity I of the peak of the (021) plane of the α crystal of MoO3 (2θ: around 27.32°, No.166363 (Inorganic Crystal Structure Database, ICSD)) A , and the RIR value K of MoO3 β crystal B and the integrated intensity I of the peak attributable to the (011) plane of the β crystal of MoO3 (2θ: around 23.01°, No.86426 (Inorganic Crystal Structure Database, ICSD)) B The content (%) of α crystals in MoO3 is calculated from the following formula (2).

[0102] Content of α crystals of MoO3 (%) = (I A / K A ) / ((I A / K A )+(I B / K B ))×100(2)

[0103] Here, the RIR values ​​may be the values ​​described in the ICSD database, and the analysis may be performed using comprehensive powder X-ray analysis software (PDXL2, manufactured by Rigaku Corporation).

[0104] The molybdenum disulfide contained in the composite of the embodiment includes a 3R crystal structure, and may include a 2H crystal structure and a 3R crystal structure.

[0105] Such a composite material including a 2H crystal structure and a 3R crystal structure is a product independently developed by the present applicant, and as its crystal structure, it has not only a 2H structure but also a rare 3R (rhombohedral crystal) structure. The 3R structure tends to have a distorted crystal structure and has more catalyst active sites, so molybdenum disulfide including a 3R crystal structure contributes to improving catalyst performance.

[0106] This composite containing a 3R crystal structure can be produced, for example, by the <<composite production method>> described later, and can synthesize molybdenum disulfide containing a 3R structure and being of the nm scale and conducive to increasing the surface area, which is difficult to achieve by crushing mineral products and synthesizing general molybdenum trioxide.

[0107] The abundance ratio of the 3R crystal structure in the crystal phase of molybdenum disulfide may be greater than 5% and less than 60%, greater than 10% and less than 60%, greater than 20% and less than 60%, or greater than 20% and less than 45%.

[0108] Regarding molybdenum disulfide having a 2H crystal structure and a 3R crystal structure, for example, it can be confirmed using an expanded Rietveld analysis software (manufactured by Malvern Panalytical, HighScore Plus) that can take into account the crystallite size. In the Rietveld analysis software, a crystal structure model including the crystallite size is used to simulate the entire diffraction pattern of XRD, and compared with the diffraction pattern of XRD obtained by experiment. In a manner in which the residual between the diffraction pattern obtained in the experiment and the diffraction pattern obtained by calculation is minimized, the crystal structure factors such as the lattice constant and atomic coordinates of the crystal structure model, the weight fraction (abundance ratio), etc. are optimized by the least squares method, and each phase of the 2H crystal structure and the 3R crystal structure is identified and quantified with high precision. Thus, in addition to the crystal structure type and its ratio calculated by the usual Rietveld analysis, the crystallite size can also be calculated. Hereinafter, in this specification, the above-mentioned analysis method using HighScore Plus is referred to as "expanded Rietveld analysis".

[0109] In addition, in the composite of the embodiment, the crystallite size of the above-mentioned 3R crystal structure obtained using the spectrum obtained by the above-mentioned XRD and by the expanded Rietveld analysis can be greater than 1 nm and less than 50 nm, and is preferably composed of a crystalline phase composed of crystallites of greater than 5 nm and less than 50 nm, and the above-mentioned crystallite size is more preferably greater than 10 nm and less than 40 nm.

[0110] In addition, in the composite of the embodiment, the crystallite size of the 2H crystal structure obtained using the spectrum obtained by the above-mentioned XRD and by the expanded Rietveld analysis is preferably greater than 1 nm and less than 50 nm, and is preferably a crystalline phase composed of crystallites greater than 1 nm and less than 50 nm, and the above-mentioned crystallite size is more preferably greater than 5 nm and less than 50 nm.

[0111] The 2H crystal structure obtained by the extended Rietveld analysis is preferably composed of a single crystal phase composed of crystallites having a predetermined crystallite size. In this case, the crystallite size of the 2H crystal structure is more preferably 1 nm to 20 nm, preferably 5 nm to 15 nm.

[0112] The crystallite size of the 2H crystal structure and the crystallite size of the 3R crystal structure can also be calculated using, for example, the half-peak width of an XRD diffraction pattern.

[0113] The abundance ratio (2H:3R) of the 2H crystal structure and the 3R crystal structure in the crystal phase obtained by extended Rietveld analysis using the spectrum obtained by the XRD is preferably 10:90 to 90:10.

[0114] From the viewpoint of the above effects, the abundance ratio (2H:3R) of the 2H crystal structure and the 3R crystal structure in the crystal phase obtained by extended Rietveld analysis using the spectrum obtained by the XRD is more preferably 10:90 to 80:20, and further preferably 40:60 to 80:20.

[0115] In addition, the 2H crystal structure obtained by the expanded Rietveld analysis may also be composed of a first crystal phase composed of crystals having a specific crystallite size, and a second crystal phase having a crystallite size smaller than that of the first crystal phase. The crystallite size of the first crystal phase of the 2H crystal structure is, for example, greater than 20 nm and less than 150 nm, or greater than 50 nm and less than 150 nm, or greater than 100 nm and less than 150 nm. However, it is preferred that the first crystal phase does not exist in the crystal phase of the 2H crystal structure, or its abundance ratio is small. In addition, the crystallite size of the second crystal phase of the 2H crystal structure is preferably greater than 1 nm and less than 20 nm, or greater than 1 nm and less than 10 nm, or greater than 5 nm and less than 15 nm.

[0116] The crystallite size of the first crystal phase of the 2H crystal structure, the crystallite size of the 3R crystal structure, and the crystallite size of the second crystal phase of the 2H crystal structure can be calculated in the same manner as described above, for example, using the half-peak width of the XRD diffraction pattern.

[0117] The abundance ratio of the first crystal phase of the 2H crystal structure, the 3R crystal structure, and the second crystal phase of the 2H crystal structure obtained by expanded Rietveld analysis using the spectrum obtained by the XRD is preferably 30 to 0:10 to 70:80 to 15, and more preferably 25 to 0:20 to 60:75 to 20.

[0118] Preferably, in the spectrum obtained by powder X-ray diffraction (XRD) using Cu-Kα rays as an X-ray source of the composite of the above embodiment, the peak near 2θ=39.5° and the peak near 49.5° are from the 2H crystal structure, the peak near 2θ=32.5°, the peak near 39.5° and the peak near 49.5° are from the 3R crystal structure, and the half-width of the peak near 2θ=39.5° and the peak near 49.5° is 1° or more. Furthermore, the above-mentioned molybdenum disulfide may also include a crystal structure other than the 2H crystal structure and the 3R crystal structure of molybdenum disulfide, such as a 1H crystal structure.

[0119] The 3R crystal structure of the above-mentioned molybdenum disulfide containing a metastable structure can be distinguished as follows: in the spectrum obtained by powder X-ray diffraction (XRD) using Cu-Kα rays as the X-ray source, the peak near 2θ=39.5° and the peak near 2θ=49.5° are both composed of synthetic peaks of the 2H crystal structure and the 3R crystal structure.

[0120] In fact, the spectrum obtained by the above-mentioned powder X-ray diffraction (XRD) is used to determine the abundance ratio of the 2H crystal structure based on the peak near 2θ=39.5° and the wide peak near 49.5°. In addition, the difference between the peak near 2θ=39.5° and the wide peak near 49.5° is optimized using the two peaks near 2θ=32.5° and the two peaks near 39.5°, thereby determining the abundance ratio of the 3R crystal structure. That is, the peak near 2θ=39.5° and the peak near 49.5° are both synthetic waves from the 2H crystal structure and the 3R crystal structure, and these synthetic waves can be used to calculate the abundance ratio of the 2H crystal structure and the 3R crystal structure of molybdenum disulfide.

[0121] The composite of the embodiment may also include an amorphous phase. The abundance ratio of the amorphous phase of the composite of the embodiment is expressed as 100 (%) - (degree of crystallinity (%)), and is preferably 5% or more, more preferably 15% or more, and further preferably 20% or more.

[0122] In the radial distribution function obtained from the extended X-ray absorption fine structure (EXAFS) spectrum of the K absorption end of molybdenum of the composite of the above embodiment, the ratio (I / II) of the peak intensity I attributed to Mo-S to the peak intensity II attributed to Mo-Mo is preferably greater than 1.0, more preferably greater than 1.1, and particularly preferably greater than 1.2.

[0123] Regardless of whether the crystal structure of molybdenum disulfide is a 2H crystal structure or a 3R crystal structure, the distance between Mo-S is almost the same due to the covalent bond, so the intensity of the peak attributed to Mo-S in the extended X-ray absorption fine structure (EXAFS) spectrum of the K absorption edge of molybdenum is the same.

[0124] On the other hand, the 2H crystal structure of molybdenum disulfide is hexagonal, so there is an identical hexagon just below the 90° hexagon of the Mo atom, so the distance between Mo-Mo is short, and the peak intensity II attributed to Mo-Mo is strong.

[0125] In contrast, the 3R crystal structure of molybdenum disulfide is a rhombohedral system, so the hexagon is not located directly below 90° of the hexagon, but is offset by half. Therefore, the distance between Mo-Mo is greater, and the peak intensity II of Mo-Mo is weaker.

[0126] In the case of a pure 2H crystal structure of molybdenum disulfide, the above ratio (I / II) is small, but as a 3R crystal structure is included, the above ratio (I / II) increases.

[0127] According to the composite of the embodiment described above, it is possible to exhibit excellent catalyst performance.

[0128] The composite of the embodiment can be used as a catalyst, and can be used as a hydrogen evolution catalyst. The composite of the embodiment can be suitably used as a hydrogen evolution catalyst in a hydrogen evolution reaction (HER) such as water electrolysis.

[0129] Furthermore, the composite material of the embodiment can be suitably used as a constituent material of a catalyst ink that can form a catalyst layer.

[0130] Furthermore, the composite of the embodiment can be suitably used as an electrode material used as a constituent material of an electrode catalyst layer.

[0131] <<Method for producing composite material>>

[0132] [Firing process]

[0133] The method for producing a composite according to the embodiment includes a calcining step of heating molybdenum trioxide in the presence of a sulfur source at a temperature of 400° C. or less. The molybdenum trioxide preferably has a β crystal structure.

[0134] As another aspect, the method for producing the composite of the embodiment may include, for example, a calcining step of heating the molybdenum trioxide particles obtained in the molybdenum trioxide particle production step described below at a temperature of 400° C. or less in the presence of a sulfur source.

[0135] The method for producing the composite may include heating molybdenum trioxide particles having a β crystal structure including molybdenum trioxide at a temperature of 100 to 800° C. in the absence of a sulfur source, and then heating at a temperature of 400° C. or less in the presence of a sulfur source.

[0136] In the calcination step, the calcination temperature in the presence of a sulfur source is 400° C. or lower, preferably lower than 350° C., more preferably 320° C. or lower, and even more preferably 310° C. or lower.

[0137] The calcination temperature may be, for example, 200°C to 400°C, 220°C to 350°C, 220°C to less than 320°C, and more preferably 250°C to 310°C.

[0138] By setting the calcination temperature to a low temperature of 400° C. or lower, the progress of the sulfurization reaction from molybdenum trioxide to molybdenum disulfide can be easily controlled, and a composite containing both molybdenum disulfide and molybdenum trioxide can be easily obtained.

[0139] The calcination time in the presence of a sulfur source may be 1 to 20 hours, 2 to 15 hours, or 3 to 10 hours as long as the sulfurization reaction proceeds appropriately and both molybdenum disulfide and molybdenum trioxide can coexist.

[0140] The calcination temperatures and calcination times exemplified above can be freely combined. Regarding the calcination conditions in the presence of a sulfur source in the calcination process, as an example, the following can be exemplified: the condition of maintaining the calcination temperature at 200°C to 400°C for 1 to 20 hours, the condition of maintaining the calcination temperature at 220°C to less than 350°C for 2 to 15 hours, the condition of maintaining the calcination temperature at 220°C to 320°C for 3 to 10 hours, the condition of maintaining the calcination temperature at 250°C to 310°C for 3 to 10 hours, etc.

[0141] The rate of temperature increase to the calcination temperature is preferably 1° C. / min or more and 50° C. / min or less, and more preferably 2° C. / min or more and 10° C. / min or less.

[0142] The average particle size of the primary particles of the molybdenum trioxide can be exemplified as being 2 nm or more and 1000 nm or less.

[0143] The average particle size of the primary particles of the molybdenum trioxide particles may be 5 nm or more and 2000 nm or less.

[0144] The average particle size of the primary particles of the molybdenum trioxide particles refers to the average primary particle size of 50 randomly selected primary particles obtained by photographing the molybdenum trioxide particles using a scanning electron microscope (SEM) or a transmission electron microscope (TEM), measuring the major axis (the Feret diameter of the longest observed portion) and the minor axis (the shorter Feret diameter in a direction perpendicular to the Feret diameter of the longest portion) of the smallest unit particle constituting the agglomerate on the two-dimensional image, and setting the average value as the primary particle size.

[0145] In the method for producing the composite, the average particle size of the primary particles of the molybdenum trioxide particles is preferably 1 μm or less. From the perspective of reactivity with sulfur, it is more preferably 600 nm or less, further preferably 400 nm or less, and particularly preferably 200 nm or less. The average particle size of the primary particles of the molybdenum trioxide particles may be 2 nm or more, 5 nm or more, or 10 nm or more.

[0146] The molybdenum trioxide particles used for the manufacture of the above-mentioned composite are preferably composed of an aggregate of primary particles having a β crystal structure of molybdenum trioxide. The above-mentioned molybdenum trioxide particles have better reactivity with sulfur than conventional molybdenum trioxide particles having only α crystals as a crystal structure. Since they contain the β crystal structure of molybdenum trioxide, the conversion rate R to MoS2 can be increased in the reaction with the sulfur source. C .

[0147] The β crystal structure of molybdenum trioxide can be confirmed by the presence of a peak attributable to the (011) plane of the β crystal of MoO3 (2θ: around 23.01°, No. 86426 (Inorganic Crystal Structure Database (ICSD))) in the following spectrum obtained by powder X-ray diffraction (XRD) using Cu-Kα rays as an X-ray source. The α crystal structure of molybdenum trioxide can be confirmed by the presence of a peak at the (021) plane of the α crystal of MoO3 (2θ: around 27.32°, No. 166363 (Inorganic Crystal Structure Database (ICSD))).

[0148] The molybdenum trioxide particles preferably have a ratio (β(011) / α(021)) of 0.1 or more of the peak intensity of the (011) plane of the β crystal of MoO3 to the peak intensity of the (021) plane of the α crystal of MoO3 (2θ: around 27.32°, No. 166363 (Inorganic Crystal Structure Database (ICSD))) in a spectrum obtained by powder X-ray diffraction (XRD) using Cu-Kα rays as an X-ray source.

[0149] The peak intensity attributable to the (011) plane of the β crystal of MoO 3 and the peak intensity attributable to the (021) plane of the α crystal of MoO 3 were read at their respective maximum intensities to determine the ratio (β(011) / α(021)).

[0150] In the molybdenum trioxide particles, the ratio (β(011) / α(021)) is preferably 0.1 to 10.0, more preferably 0.2 to 10.0, and particularly preferably 0.4 to 10.0.

[0151] The β-crystal structure of molybdenum trioxide can also be determined by Raman spectroscopy, which shows a wave number of 773 cm -1 、848 cm -1 and 905 cm -1 The α crystal structure of molybdenum trioxide can be confirmed by the presence of a peak at 663 cm -1 、816 cm -1 and 991 cm -1 The presence of the peak at was confirmed.

[0152] Examples of the sulfur source include sulfur and hydrogen sulfide, and these may be used alone or in combination of two.

[0153] In the method for producing the above-mentioned composite, the feeding ratio (molar ratio) of the amount of S in the above-mentioned sulfur source to the amount of MoO3 in the above-mentioned molybdenum trioxide particles can be in the range of sulfur (S) / molybdenum trioxide (MoO3) = 2 to 30, in the range of 3 to 15, or in the range of 4 to 6.

[0154] Regarding the charge amount of the sulfur source, there is a tendency that the amount of unreacted molybdenum oxide present is suppressed as the excess amount of the sulfur source increases.

[0155] On the other hand, there is a tendency that the amount of unreacted molybdenum oxide present increases as the values ​​of the calcination temperature and calcination time decrease.

[0156] In the method for producing the composite, the molybdenum trioxide particles preferably contain 99.5% by mass or more of MoO3 as measured by X-ray fluorescence (XRF). C , a high-purity complex with good storage stability can be obtained without worrying about the formation of disulfide from impurities.

[0157] The specific surface area of ​​the molybdenum trioxide particles measured by the BET method is preferably 10 m 2 / g~100 m 2 / g.

[0158] In the above-mentioned molybdenum trioxide particles, the above-mentioned specific surface area is preferably 10 m 2 / g or more, more preferably 20 m 2 / g or more, more preferably 30 m 2 In the above molybdenum trioxide particles, the molybdenum trioxide particles preferably have a particle size of 100 m / g or more from the perspective of ease of manufacture. 2 / g or less, can be 90 m 2 / g or less, and can also be 80 m 2 / g or less.

[0159] The molybdenum trioxide particles preferably have an intensity I of a peak attributable to Mo—O in a radial distribution function obtained from an extended X-ray absorption fine structure (EXAFS) spectrum of the K absorption end of molybdenum. O and the peak intensity II attributed to Mo-Mo O The ratio of O / II O ) is greater than 1.1.

[0160] Regarding the intensity of the peak attributed to Mo-O O and the peak intensity II attributed to Mo-Mo O , read the maximum intensity of the peaks respectively, and calculate the above ratio (I O / II O The above ratio (I O / II O ) is considered to be the standard for obtaining the β crystal structure of MoO3 in molybdenum trioxide particles. O / II O ) is larger, the reactivity with sulfur is better.

[0161] In the above molybdenum trioxide particles, the above ratio (I O / II O ) is preferably 1.1 to 5.0, can be 1.2 to 4.0, and can also be 1.2 to 3.0.

[0162] According to the method for producing the composite of the embodiment described above, the composite of the embodiment can be produced. In addition, the method for producing the composite of the embodiment has the following outstanding advantages, such as: 1) no organic solvent is required in the reaction, 2) unlike the general hydrothermal method, the composite can be recovered even without filtering and other operations, and 3) easy mass production.

[0163] (Method for producing molybdenum trioxide particles)

[0164] The method for producing the composite according to the embodiment may further include a molybdenum trioxide production step of producing the molybdenum trioxide particles.

[0165] The molybdenum trioxide particles may be produced by a molybdenum trioxide production process, which includes gasifying a molybdenum oxide precursor compound to form molybdenum trioxide vapor, and cooling the molybdenum trioxide vapor.

[0166] The method for producing the above-mentioned molybdenum trioxide particles preferably includes calcining a raw material mixture containing a molybdenum oxide precursor compound and a metal compound other than the above-mentioned molybdenum oxide precursor compound, gasifying the above-mentioned molybdenum oxide precursor compound to form molybdenum trioxide vapor, and the ratio of the above-mentioned metal compound to 100% by mass of the above-mentioned raw material mixture is less than 70% by mass when converted to oxide.

[0167] The above-mentioned method for producing molybdenum trioxide particles can be appropriately carried out using a production apparatus 1 shown in FIG. 1 .

[0168] FIG. 1 is a schematic diagram showing an example of an apparatus for producing molybdenum trioxide particles which are a raw material of the composite according to the present embodiment.

[0169] As shown in FIG. 1 , the manufacturing device 1 comprises: a calcining furnace 2, which calcines a molybdenum trioxide precursor compound or the raw material mixture to gasify the molybdenum trioxide precursor compound; a cross-shaped cooling pipe 3, which is connected to the calcining furnace 2, and atomizes the molybdenum trioxide vapor formed by the calcination gasification; and a recovery machine 4, which is a recovery means for recovering the molybdenum trioxide particles atomized by the cooling pipe 3. At this time, the calcining furnace 2 and the cooling pipe 3 are connected via an exhaust port 5. In addition, the cooling pipe 3 is respectively provided with an opening adjustment damper 6 at the left end at the external gas intake port (not shown), and an observation window 7 is provided at the upper end. An exhaust device 8 as a first air supply means is connected to the recovery machine 4. The exhaust device 8 exhausts air, thereby sucking the internal gas of the recovery machine 4 and the cooling pipe 3, and the external gas is blown into the cooling pipe 3 from the opening adjustment damper 6 of the cooling pipe 3. That is, the exhaust device 8 performs a suction function, thereby passively sending air to the cooling pipe 3. It should be noted that the production apparatus 1 may also include an external cooling device 9, which can arbitrarily control the cooling conditions of the molybdenum trioxide vapor generated by the sintering furnace 2.

[0170] By opening the opening adjustment damper 6, air is sucked in from the external air intake port, and the molybdenum trioxide vapor gasified by the sintering furnace 2 is cooled in the air environment to form molybdenum trioxide particles, thereby making the above ratio (I O / II O ) is greater than 1.1, the β crystal structure of MoO3 is easily obtained in the molybdenum trioxide particles. In the case of using liquid nitrogen to cool the molybdenum trioxide vapor, the cooling of the molybdenum trioxide vapor in a nitrogen environment with a low oxygen concentration is likely to increase the oxygen defect density and reduce the above ratio (IO / II O ).

[0171] The molybdenum oxide precursor compound is not particularly limited as long as it is a molybdenum oxide precursor compound that forms molybdenum trioxide vapor by calcining, and examples thereof include metallic molybdenum, molybdenum trioxide, molybdenum dioxide, molybdenum sulfide, ammonium molybdate, phosphomolybdic acid (H3PMo 12 O 40 ), silicomolybdic acid (H4SiMo 12 O 40 ), aluminum molybdate, silicon molybdate, magnesium molybdate (MgMo n O 3n+1 (n = 1 ~ 3)), sodium molybdate (Na2Mo n O 3n+1 (n = 1 ~ 3)), titanium molybdate, iron molybdate, potassium molybdate (K2Mo n O 3n+1 (n = 1 ~ 3)), zinc molybdate, boron molybdate, lithium molybdate (Li2Mo n O 3n+1 (n=1-3)), cobalt molybdate, nickel molybdate, manganese molybdate, chromium molybdate, cesium molybdate, barium molybdate, strontium molybdate, yttrium molybdate, zirconium molybdate, copper molybdate, etc. These molybdenum oxide precursor compounds can be used alone or in combination of two or more. The form of the molybdenum oxide precursor compound is not particularly limited, for example, it can be a powder such as molybdenum trioxide, or a liquid such as an ammonium molybdate aqueous solution, but preferably a powder with good handling properties and good energy efficiency.

[0172] As the molybdenum trioxide precursor compound, it is particularly preferred to use commercially available α-crystal molybdenum trioxide. In addition, when ammonium molybdate is used as the molybdenum oxide precursor compound, it is converted into thermodynamically stable molybdenum trioxide by calcination, so the molybdenum oxide precursor compound that is gasified is the above-mentioned molybdenum trioxide.

[0173] Molybdenum trioxide vapor can also be formed by calcining a raw material mixture containing a molybdenum oxide precursor compound and a metal compound other than the molybdenum oxide precursor compound.

[0174] Among them, the molybdenum oxide precursor compound preferably contains molybdenum trioxide from the viewpoint of easily controlling the purity, average particle size of primary particles, and crystal structure of the obtained molybdenum trioxide powder.

[0175] Although there is a case where the molybdenum oxide precursor compound and a metal compound other than the above-mentioned molybdenum oxide precursor compound generate an intermediate, in this case, the intermediate is also decomposed by calcination, and molybdenum trioxide can be vaporized in a thermodynamically stable form.

[0176] As the metal compound other than the molybdenum oxide precursor compound, an aluminum compound is preferably used because it can prevent damage to the sintering furnace. In order to improve the purity of the molybdenum trioxide particles, no metal compound other than the molybdenum oxide precursor compound may be used.

[0177] The metal compound other than the molybdenum oxide precursor compound is not particularly limited, and examples thereof include aluminum compounds, silicon compounds, titanium compounds, magnesium compounds, sodium compounds, potassium compounds, zirconium compounds, yttrium compounds, zinc compounds, copper compounds, iron compounds, etc. Among them, the aluminum compound, silicon compound, titanium compound or magnesium compound is preferably used as the metal compound.

[0178] Although there is a case where the molybdenum oxide precursor compound and a metal compound other than the above-mentioned molybdenum oxide precursor compound generate an intermediate, in this case, the intermediate is also decomposed by calcination, and molybdenum trioxide can be vaporized in a thermodynamically stable form.

[0179] As the metal compound other than the molybdenum oxide precursor compound, an aluminum compound is preferably used because it can prevent damage to the firing furnace. In the above production method, in order to improve the purity of the molybdenum trioxide powder, the metal compound other than the molybdenum oxide precursor compound may not be used.

[0180] Examples of the aluminum compound include aluminum chloride, aluminum sulfate, basic aluminum acetate, aluminum hydroxide, boehmite, pseudo-boehmite, transition alumina (γ-alumina, δ-alumina, θ-alumina, etc.), α-alumina, and mixed alumina having two or more crystal phases.

[0181] When a raw material mixture containing a molybdenum oxide precursor compound and a metal compound other than the molybdenum oxide precursor compound is calcined, the content ratio of the molybdenum oxide precursor compound relative to 100 mass % of the raw material mixture is preferably 40 mass % or more and 100 mass % or less, may be 45 mass % or more and 100 mass % or less, and may also be 50 mass % or more and 100 mass % or less.

[0182] The calcination temperature varies depending on the molybdenum oxide precursor compound, metal compound, and desired molybdenum trioxide particles used, but is generally preferably set to a temperature at which the intermediate can be decomposed. For example, when a molybdenum compound is used as the molybdenum oxide precursor compound and an aluminum compound is used as the metal compound, aluminum molybdate may be formed as an intermediate, so the calcination temperature is preferably 500 to 1500° C., more preferably 600 to 1550° C., and further preferably 700 to 1600° C.

[0183] The firing time is not particularly limited, and may be, for example, 1 minute to 30 hours, 10 minutes to 25 hours, or 100 minutes to 20 hours.

[0184] The heating rate varies depending on the properties of the molybdenum oxide precursor compound used, the above-mentioned metal compound, and the desired molybdenum trioxide particles, but from the perspective of manufacturing efficiency, it is preferably 0.1°C / min to 100°C / min, more preferably 1°C / min to 50°C / min, and further preferably 2°C / min to 10°C / min.

[0185] The internal pressure in the calcining furnace is not particularly limited, and may be positive pressure or reduced pressure, but from the viewpoint of appropriately discharging the molybdenum oxide precursor compound from the calcining furnace to the cooling pipe, calcining is preferably carried out under reduced pressure. As a specific degree of reduced pressure, preferably -5000 Pa to -10 Pa, more preferably -2000 Pa to -20 Pa, and further preferably -1000 Pa to -50 Pa. If the degree of reduced pressure is above -5000 Pa, high air tightness and mechanical strength of the calcining furnace will not be excessively required, and manufacturing costs can be reduced, so it is preferred. On the other hand, if the degree of reduced pressure is below -10 Pa, it is possible to prevent the molybdenum oxide precursor compound from clogging the discharge port of the calcining furnace, so it is preferred.

[0186] In addition, when blowing gas into the calcination furnace during calcination, the temperature of the gas to be blown is preferably 5 to 500°C, and more preferably 10 to 100°C.

[0187] The blowing rate of the gas is preferably 1 L / min or more and 500 L / min or less, and more preferably 10 L / min or more and 200 L / min or less, relative to the effective volume of 100 L of the sintering furnace.

[0188] The temperature of the vaporized molybdenum trioxide vapor varies depending on the type of molybdenum oxide precursor compound used, but is preferably 200 to 2000° C., and more preferably 400 to 1500° C. It should be noted that if the temperature of the vaporized molybdenum trioxide vapor is 2000° C. or less, there is a tendency that the vaporized molybdenum trioxide vapor can be easily particle-formed by blowing external gas (0 to 100° C.) in the cooling pipe.

[0189] The discharge rate of molybdenum trioxide vapor from the calcining furnace can be controlled according to the amount of the molybdenum oxide precursor compound used, the amount of the metal compound, the temperature of the calcining furnace, the blowing of gas into the calcining furnace, and the diameter of the exhaust port of the calcining furnace. Although it varies depending on the cooling capacity of the cooling pipe, the discharge rate of molybdenum trioxide vapor from the calcining furnace to the cooling pipe is preferably 0.001 g / min or more and 100 g / min or less, and more preferably 0.1 g / min or more and 50 g / min or less.

[0190] The content of molybdenum trioxide vapor contained in the gas exhausted from the calcining furnace is preferably 0.01 mg / L or more and 1000 mg / L or less, and more preferably 1 mg / L or more and 500 mg / L or less.

[0191] Next, the molybdenum trioxide vapor is cooled and formed into particles.

[0192] The cooling of the molybdenum trioxide vapor is carried out by making the cooling pipe become low temperature. At this time, as cooling means, cooling by blowing gas to the cooling pipe as mentioned above, cooling by a cooling mechanism possessed by the cooling pipe, cooling by an external cooling device, etc. can be listed.

[0193] The cooling of the molybdenum trioxide vapor is preferably carried out in an air environment. By cooling the molybdenum trioxide vapor in an air environment to produce molybdenum trioxide particles, the above ratio (I O / II O ) is greater than 1.1, the β crystal structure of MoO3 is easily obtained in the molybdenum trioxide particles.

[0194] The cooling temperature (temperature of the cooling pipe) is not particularly limited, but is preferably -100 to 600°C, more preferably -50 to 400°C.

[0195] The cooling rate of the molybdenum trioxide vapor is not particularly limited, but is preferably 100°C / s or more and 100,000°C / s or less, and more preferably 1,000°C / s or more and 50,000°C / s or less. It should be noted that the faster the cooling rate of the molybdenum trioxide vapor, the more molybdenum trioxide particles with smaller particle size and larger specific surface area can be obtained.

[0196] When the cooling means is cooling by blowing gas to the cooling pipe, the temperature of the blown gas is preferably -100 to 300°C, more preferably -50 to 100°C.

[0197] In addition, the blowing speed of the gas is preferably 0.1 m 3 / min or more and 20 m 3 / min or less, more preferably 1 m 3 / min or more and 10 m 3 / min or less. If the gas blowing speed is 0.1 m 3 / min or more, a higher cooling rate can be achieved and clogging of the cooling pipe can be prevented, so it is preferred. On the other hand, if the gas blowing speed is 20 m 3 / min or less, there is no need for the expensive first air supply means (exhaust fan, etc.), which can reduce the manufacturing cost and is therefore preferred.

[0198] The particles obtained by cooling the molybdenum trioxide vapor are transported to a recovery machine for recovery.

[0199] In the method for producing molybdenum trioxide particles, the particles obtained by cooling the molybdenum trioxide vapor may be calcined again at a temperature of 100 to 320°C.

[0200] That is, the molybdenum trioxide particles obtained in the above-mentioned method for producing molybdenum trioxide particles may be calcined again at a temperature of 100 to 320°C. The calcination temperature for the calcination again may be 120 to 280°C, or 140 to 240°C. The calcination time for the calcination again may be, for example, 1 minute to 4 hours, 10 minutes to 5 hours, or 100 minutes to 6 hours. However, due to the calcination again, part of the β crystal structure of the molybdenum trioxide disappears. If the calcination is performed at a temperature above 350°C for 4 hours, the β crystal structure in the molybdenum trioxide particles disappears, and the above-mentioned ratio (β (011) / α (021)) becomes 0, thereby impairing the reactivity with sulfur.

[0201] According to the method for producing molybdenum trioxide particles described above, molybdenum trioxide particles suitable for production of the above-mentioned composite can be produced.

[0202] [Cleaning process]

[0203] The method for producing the composite of the embodiment may also include a cleaning step of removing the sulfur source after the calcining step. The cleaning step can remove the excess sulfur source used in the calcining step. The cleaning step may be repeated two or more times as needed.

[0204] The method for removing the sulfur source is not particularly limited, and a method of bringing a solvent capable of dissolving the sulfur source into contact with the product obtained in the calcination step to transfer the sulfur source into the solvent can be cited. The above-mentioned solvent can be toluene, hexane, carbon disulfide, etc., and the excess sulfur source can be removed by washing with the solvent.

[0205] For example, when elemental sulfur is used as a sulfur source, the ratio of the content of elemental sulfur in the sulfur element in the produced composite can be reduced by performing the washing step.

[0206] <<Hydrogen Evolution Catalyst>>

[0207] The composite of the embodiment can be suitably used as a catalyst in the hydrogen evolution reaction (HER) (sometimes referred to as a "hydrogen evolution catalyst" in this specification). In addition, the composite of the embodiment can also be used as a hydrogen evolution catalyst in combination with a conductive material. That is, as a preferred hydrogen evolution catalyst, for example, a hydrogen evolution catalyst containing the composite of the embodiment can be cited, and the above-mentioned hydrogen evolution catalyst can also contain a conductive material in addition to the composite of the embodiment. The catalyst activity of the hydrogen evolution catalyst containing the composite of the embodiment and the conductive material in the hydrogen evolution reaction (HER) is further increased.

[0208] The conductive material mentioned above may be a known conductive material.

[0209] Examples of the conductive material include carbon and metals having high conductivity.

[0210] The conductive material contained in the hydrogen evolution catalyst may be only one kind or two or more kinds.

[0211] Examples of the conductive material include carbon black such as acetylene black, Cabot black, and Ketjen black, graphite, carbon fiber, and metal powder. Ketjen black is excellent because it has a high specific surface area and conductivity and can also suppress aggregation of molybdenum sulfide.

[0212] Examples of the metal of the conductive material include gold, silver, copper, aluminum, rhodium, molybdenum, tungsten, iron, nickel, cobalt, and indium.

[0213] The metals contained in the hydrogen evolution catalyst as the conductive material may be only one kind or two or more kinds.

[0214] For example, the hydrogen evolution catalyst may contain no metal but contain carbon as the conductive material, may contain no carbon but contain metal as the conductive material, or may contain both metal and carbon as the conductive material.

[0215] In the hydrogen evolution catalyst, the content of the conductive material is preferably 0.1 to 100 parts by mass, and more preferably 0.5 to 50 parts by mass, based on 100 parts by mass of the composite of the embodiment.

[0216] In the hydrogen evolution catalyst, the total content of the composite of the embodiment and the above-mentioned conductive material relative to the total mass (100 mass %) of the hydrogen evolution catalyst is preferably 80 mass % or more, more preferably 90 mass % or more, and further preferably 95 mass % or more, for example, it can be any one of 97 mass % or more and 99 mass % or more, or it can be 100 mass %. By making the above ratio above the above lower limit, the catalytic activity of the hydrogen evolution catalyst in the hydrogen evolution reaction (HER) is further increased. The above ratio can be 100 mass % or less.

[0217] <<Catalyst ink>>

[0218] The above-mentioned hydrogen evolution catalyst is suitable as a component contained in the catalyst ink.

[0219] The catalyst ink of the embodiment contains the composite of the embodiment and a solvent.

[0220] The catalyst ink of the embodiment may contain the composite of the embodiment, a polymer electrolyte, and a solvent.

[0221] The catalyst ink of the present embodiment may further contain a conductive material. Examples of the type and content of the conductive material include the types and contents of the conductive materials exemplified above.

[0222] The catalyst ink can be applied to, for example, a working electrode substrate to form a catalyst layer.

[0223] As the polymer electrolyte, a polymer electrolyte commonly used when forming a catalyst layer can be used. Specifically, examples thereof include perfluorocarbon polymers having a sulfonic acid group (e.g., Nafion (registered trademark)), hydrocarbon polymer compounds having a sulfonic acid group, polymer compounds doped with an inorganic acid such as phosphoric acid, organic / inorganic hybrid polymers partially substituted with a proton conductive functional group, and proton conductors formed by impregnating a polymer matrix with a phosphoric acid solution or a sulfuric acid solution.

[0224] As the solvent, there can be cited a solvent that can disperse the composite of the embodiment and can be coated on a working electrode substrate to form a catalyst layer. As the above-mentioned solvent, preferably, it contains alcohols such as 1-propanol, 2-propanol, 1-butanol, 2-butanol, 1-pentanol, 2-pentanol, 1-hexanol, 2-hexanol, 1-heptanol, and 2-heptanol.

[0225] Example

[0226] Next, the present invention will be described in further detail with reference to examples, but the present invention is not limited to the following examples.

[0227] [Synthesis example 1]

[0228] (Manufacturing of molybdenum trioxide particles)

[0229] A sintering furnace equivalent to a heat-resistant container, a cooling pipe provided with an external gas supply port, and a dust collector for collecting molybdenum oxide were prepared. Molybdenum oxide was produced using an RHK simulator (manufactured by Noritake Company Limited) as the sintering furnace and a VF-5N dust collector (manufactured by Amano Co., Ltd.) as the dust collector.

[0230] 1.5 kg of aluminum hydroxide (manufactured by Nippon Light Metal Co., Ltd.) and 1 kg of molybdenum trioxide (manufactured by Nippon Muki Co., Ltd.) were mixed and then added to the sagger. The sintering furnace, cooling pipe, and dust collector were connected and sintered at a temperature of 1100°C for 10 hours. During the sintering, external air was introduced from the side and bottom of the sintering furnace (blowing rate: 150 L / min, external air temperature: 25°C). Since molybdenum trioxide evaporates in the furnace, it is cooled near the dust collector and precipitated in the form of particles, so the molybdenum trioxide is recovered by the dust collector.

[0231] After the firing, 1.0 kg of alumina, which is a blue powder, was taken out from the sagger, and 0.8 kg of molybdenum trioxide was recovered by a dust collector.

[0232] The primary particle size of the recovered molybdenum trioxide was 1 μm or less, and the purity of the molybdenum trioxide was confirmed to be 99.8% by fluorescent X-ray measurement.

[0233] [Example 1]

[0234] (Manufacturing of composite particles)

[0235] 500 mg of molybdenum trioxide particles obtained in the above-mentioned synthesis example 1 and 556 mg of sulfur (Kanto Chemical Co., Ltd. reagent, S) are put into a crucible and mixed until uniform. The amount of MoO3 in the molybdenum trioxide particles used is 1 mol, and the amount of S in sulfur is 5 mol. After mixing, a lid is placed on the crucible, and it is put into a nitrogen environment furnace for sintering. The sintering conditions are to increase the temperature at a rate of 5°C / min from a room temperature of 25°C, and to maintain it for 4 hours from the time point when 300°C is reached. Nitrogen is blown at 0.2 ml / min during the sintering process. Thereafter, the furnace is cooled by natural cooling to obtain the product. After ultrasonic cleaning of the obtained product in toluene, the cleaning operation of replacing toluene is performed three times, and then vacuum drying is performed to obtain the composite particles of Example 1.

[0236] [Examples 2 to 5]

[0237] Except that the amount of sulfur in the raw material and the calcination temperature used in Example 1 were set to the conditions described in Table 1, the same procedure as in Example 1 was carried out to obtain composite particles of Examples 2 to 5.

[0238] [Reference Example 1]

[0239] Except that the calcination temperature in Example 1 was set to the conditions described in Table 1, the same procedure as in Example 1 was carried out to obtain particles of Reference Example 1.

[0240] [Reference Example 2]

[0241] The molybdenum trioxide particles obtained in the above-mentioned Synthesis Example 1 were used as the molybdenum trioxide particles of Reference Example 2.

[0242] [Comparative Example 1]

[0243] As the molybdenum trioxide particles of Comparative Example 1, commercially available molybdenum trioxide particles (manufactured by Nippon Inorganic Chemical Industry Co., Ltd.) were used.

[0244] [Comparative Example 2]

[0245] As the molybdenum disulfide particles of Comparative Example 2, commercially available molybdenum disulfide particles (manufactured by Kanto Chemical Co., Ltd.) were used.

[0246] The particles of Examples 1 to 5, Reference Examples 1 to 2, and Comparative Examples 1 to 2 were used as samples and the following evaluations were performed.

[0247] <<Evaluation>>

[0248] [XRF analysis]

[0249] Using a fluorescent X-ray analyzer Primus IV (manufactured by Rigaku Co., Ltd.), take about 20 to 30 mg of the sample onto filter paper, cover it with a PP film and perform composition analysis. Based on the sulfur content obtained by the XRF analysis results, the molybdenum disulfide conversion amount (mass %) relative to 100% by mass of the sample particles is calculated. Based on the molybdenum content minus the molybdenum corresponding to the molybdenum disulfide conversion amount, the molybdenum trioxide conversion amount (mass %) relative to 100% by mass of the sample particles is calculated.

[0250] [XRD crystal structure determination]

[0251] The sample was filled into a measurement sample holder having a depth of 0.5 mm, and the holder was placed in a wide-angle X-ray diffraction (XRD) apparatus (Ultima IV manufactured by Rigaku Corporation) and measured under the conditions of Cu / Kα radiation, 40 kV / 40 mA, scanning speed 2θ=2° / min, and scanning range 2θ=10° or more and 70° or less.

[0252] [Determination of crystallite size]

[0253] SmartLab 9kW (manufactured by Rigaku Co., Ltd.) was used as an X-ray diffraction device, a scintillation counter detector was used as a detector, and PDXL2 was used as the analysis software for measurement. The measurement method was the 2θ / θ method, and the average crystallite size of molybdenum disulfide was calculated using the Scherrer formula based on the half-width of the peak appearing at 2θ=14.4°±0.5°. The average crystallite size of molybdenum trioxide was calculated using the Scherrer formula based on the half-width of the peak appearing at 2θ=12.7°±0.5°. It should be noted that as measurement conditions, the scanning speed (2θ) was 2.0° / min, the scanning range (2θ) was 10-70°, the step (2θ) was 0.02°, and the device standard width was set to none.

[0254] [Conversion rate R C ]

[0255] Conversion rate of sample to MoS2 R C It can be obtained by the RIR (reference intensity) method based on the spectrum data obtained by X-ray diffraction (XRD) measurement of the sample. The RIR value K of molybdenum disulfide (MoS2) is used. A and the integrated intensity I of the peak near 2θ=14.4°±0.5° attributable to the (002) plane or (003) plane of molybdenum disulfide (MoS2) A , and each molybdenum oxide (MoO3 as a raw material and Mo9O as a reaction intermediate) 25 、Mo4O 11 , MoO2, etc.) B and each molybdenum oxide (MoO3 as raw material and Mo9O as reaction intermediate) 25 、Mo4O 11 , MoO2, etc.) is the integrated intensity I B The conversion rate R to MoS2 is calculated by the following formula (1): C .

[0256] R C (%) = (I A / K A ) / ((I A / K A )+Σ(I B / K B ))×100(1)

[0257] Here, the RIR values ​​were the values ​​listed in the Inorganic Crystal Structure Database (ICSD) (created by the Institute of Chemical Information), and the analysis was performed using comprehensive powder X-ray analysis software (manufactured by Rigaku Corporation, PDXL2).

[0258] [Measurement of BET specific surface area]

[0259] The specific surface area was measured using a specific surface area meter (BELSORP-mini, manufactured by Microtrac BEL) and the surface area per 1 g of the sample measured from the amount of nitrogen adsorption by the BET method was calculated as the specific surface area.

[0260] [Median particle size D 50 Determination of

[0261] 0.1 g of the sample powder was added to 20 cc of acetone, and ultrasonic treatment was performed in an ice bath for 4 hours. Then, the concentration was appropriately adjusted with acetone to a range that could be measured by a dynamic light scattering particle size distribution measuring device (manufactured by MicrotracBEL, Nanotrac Wave II) to obtain a measurement sample. Using this measurement sample, the particle size distribution in the range of 0.0001 μm to 10 μm was measured by a dynamic light scattering particle size distribution measuring device, and the particle size at which the volume cumulative % ratio was 50%, i.e., the median particle size D, was calculated. 50 It should be noted that the median particle size D 50 For particles larger than 10 μm (Comparative Example 2), the solution was adjusted in the same manner, and the particle size distribution in the range of 0.015 μm to 500 μm was measured using a laser diffraction particle size distribution analyzer (manufactured by Shimadzu Corporation, SALD-7000), and the median particle size D was calculated. 50 .

[0262] Table 1 shows the results of the above measurements.

[0263] [Table 1]

[0264]

[0265] The particles of Examples 1 to 5, Reference Examples 1 to 2, and Comparative Examples 1 to 2 have MoO3 content, MoS2 content, conversion rate R C , BET specific surface area, average MoS2 crystallite size, average MoO3 crystallite size, and D 50 .

[0266] The results of the XRD analysis are shown in Fig. 2. The XRD spectra of the composite particles of Examples 1 to 5 include both a peak attributable to MoS2 and a peak attributable to MoO3.

[0267] In addition, from the XRD patterns of the particles of Examples 1 to 5 and Reference Example 1, peaks near 2θ=39.5° and 49.5° from the 2H crystal structure of MoS2, and peaks near 2θ=32.5°, 39.5°, and 49.5° from the 3R crystal structure of MoS2 were confirmed. It was confirmed that the particles of Examples 1 to 5 and Reference Example 1 contained the 2H crystal structure and 3R crystal structure of MoS2.

[0268] FIG. 3 shows an observation image of the composite particles of Example 1 obtained by a transmission electron microscope (TEM, manufactured by JEOL Ltd., JEM-1400).

[0269] FIG. 4 shows a HAADF-STEM image (transmission electron image, manufactured by JEOL Ltd., JEM-ARM300F) of the composite particles of Example 1 and the results of elemental mapping by energy dispersive X-ray spectroscopy (EDS).

[0270] From the results of element mapping, it can be seen that the area with a low amount of O element and a high amount of S element exists on the surface of the composite particles and near the surface (refer to the arrow in Figure 3). That is, the closer the area is to the surface of the composite particles, the higher the content of MoS2 is than MoO3, and MoS2 is concentrated on the surface of the composite particles. Therefore, the following possibility is considered: during the sintering process, the MoO3 of the particles of Synthesis Example 1 of the raw material is sequentially changed from the surface layer in contact with the sulfur source to MoS2.

[0271] (Manufacture of catalyst ink)

[0272] Inks were prepared using the particles of Examples 1 to 5, Reference Examples 1 to 2, and Comparative Examples 1 to 2 as raw materials, and the catalytic performance in the hydrogen evolution reaction (HER) was evaluated according to the following method.

[0273] 4 mg of the particles obtained above (any of the particles of Examples 1 to 5, Reference Examples 1 to 2, and Comparative Examples 1 to 2), carbon black (Ketjen Black, product number: EC300J, median particle size D 200, manufactured by Lion Specialty Chemical Co., Ltd.) and the like were mixed. 50: 40 nm) 2 mg, 5% Nafion dispersion (Fujifilm Wako Pure Chemical Industries, Ltd., Nafion dispersion solution) 40 μL, and 1 mL of ethanol were mixed and ultrasonicated for 1 hour to disperse the particles, thereby preparing ink (dispersion). 20 μL of the obtained ink was applied to the electrode surface, and after the surface liquid was naturally dried, it was transferred to a vacuum dryer and dried at 60°C for more than 6 hours to obtain a test electrode. The hydrogen evolution reaction (HER) activity of the obtained test electrode was evaluated by a three-electrode method. The evaluation conditions were performed by the LSV method with a scanning voltage range of -0.3 V to 0 V and a scanning speed of 5 mV / S.

[0274] Table 1 shows the evaluation results of the above catalyst performance.

[0275] The inks containing the composite particles of Examples 1 to 5 had a current density of 10 mAcm-1 compared to the inks containing the particles of Reference Examples 1 to 2 or Comparative Examples 1 to 2. -2 The overvoltage value at 0.1 V was low (the overvoltage value in Reference Example 2 and Comparative Examples 1 and 2 could not be measured), and the current density value at -0.3 V was high.

[0276] It can be seen from the above that the composites of Examples 1 to 5 can exert excellent hydrogen evolution catalyst activity.

[0277] Each configuration and combination thereof in each embodiment is an example, and addition, omission, substitution, and other changes of configurations can be made without departing from the gist of the present invention. The present invention is not limited to each embodiment but only to the scope of claims.

[0278] Explanation of symbols

[0279] 1: Manufacturing device

[0280] 2: Firing furnace

[0281] 3: Cooling piping

[0282] 4: Recycling Machine

[0283] 5: Exhaust port

[0284] 6: Opening adjustment damper

[0285] 7: Observation window

[0286] 8: Exhaust device

[0287] 9: External cooling device

Claims

1. A composite comprising molybdenum disulfide and molybdenum trioxide, The molybdenum disulfide comprises a 3R crystal structure, The content of molybdenum trioxide-equivalent value B calculated from the molybdenum content determined by XRF analysis of the composite is 5 to 90% by mass relative to the total mass of the composite.

2. The composite according to claim 1, wherein The molybdenum disulfide has an average crystallite size of 50 nm or less, which is determined from a peak at 2θ=14.4°±0.5° obtained by X-ray diffraction measurement.

3. The composite according to claim 1 or 2, wherein: The average crystallite size of the molybdenum trioxide determined from a peak at 2θ=12.7°±0.5° obtained by X-ray diffraction measurement is 50 nm or less.

4. The composite according to claim 1 or 2, wherein: The median particle size D of the composite obtained by dynamic light scattering method is 50 Below 1000 nm.

5. The composite according to claim 1 or 2, wherein The specific surface area of ​​the composite measured by the BET method is 5 m 2 / g and above 200 m 2 / g or less.

6. The composite according to claim 1 or 2, wherein: The ratio A / B of the molybdenum disulfide conversion value A calculated from the sulfur content determined by XRF analysis of the composite to the molybdenum trioxide conversion value B calculated from the molybdenum content determined by XRF analysis of the composite is 0.1 to 50 on a mass basis.

7. The composite according to claim 1 or 2, wherein: The content of molybdenum disulfide equivalent value A calculated from the sulfur content determined by XRF analysis of the composite is 10 to 95% by mass relative to the total mass of the composite.

8. The composite according to claim 1 or 2, wherein The ratio of the content of elemental sulfur to the total content of sulfur elements in the composite is 10% or less on a molar basis.

9. The composite according to claim 1 or 2, which is used as a hydrogen evolution catalyst. 10 . A catalyst ink comprising the composite according to claim 1 or 2 and a solvent.

11. A method for producing the composite according to claim 1 or 2, comprising a calcining step of heating molybdenum trioxide at a temperature of 400°C or less in the presence of a sulfur source. 12 . The method for producing a composite according to claim 11 , further comprising a cleaning step of removing the sulfur source after the calcining step.

13. The method for producing a composite according to claim 11, wherein: The specific surface area of ​​the molybdenum trioxide measured by the BET method is 10 m 2 / g and above 100 m 2 / g or less.

Citation Information

Patent Citations

  • Molybdenum disulfide nanoflower and its manufacturing method

    JP2004277199A

  • Method and apparatus for the production of inorganic fullerene-like nanoparticles

    JP2004512250A

  • Information processing device, information processing method, and program

    JP2022146943A